Utvärdering av traktplanering på SCA Skog - Sjödin, Mattias (SLU/School for Forest Management, 2012)
This study is an analysis of a survey that harvester operators working for SCA Ångermanland Skogsförvaltning have been participating in. The purpose of this study is to try to show the harvester operators opinion about the forestry planning that SCA provides. Hopefully will this information lead to suggestion about what part of the forestry planning needs to be improved, if any is needed? Unfortunately only 30 / 60 questionnaire has been returned so no conclusion can be made, except about those who have answered the survey. The answers of the survey indicate a number of areas that needs to be improved. The marked routes needs to be more visible and the education about timber landings must be enhanced. A simple checklist about what needs to be written in the textdirective will be beneficial. If the exchange of information between SCA and the entrepreneurs is improved, the productivity of the harvesting group can be increased. The forestry planning has a key role in the pursuit for a high quality and effective forestry.